The earth is weeping : the epic story of the Indian wars for the American West - Cozzens, Peter, 1957- (Alfred A. Knopf, 2016)
"With the end of the Civil War, the nation recommenced its expansion onto traditional Indian tribal lands, setting off a wide-ranging conflict that would last more than three decades. In an exploration of the wars and negotiations that destroyed tribal ways of life even as they made possible the emergence of the modern United States, Peter Cozzens gives us both sides in comprehensive and singularly intimate detail. He illuminates the encroachment experienced by the tribes and the tribal conflicts over whether to fight or make peace, and explores the squalid lives of soldiers posted to the frontier and the ethical quandaries faced by generals who often sympathized with their native enemies"--Amazon.com.